2020
DOI: 10.1038/s41592-020-0731-1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of atom resolvability in cryo-EM maps with Q-scores

Abstract: CryoEM density maps are now at the point where resolvability of individual atoms can be achieved. However, resolvability is not necessarily uniform throughout the map. We introduce a quantitative parameter to characterize the resolvability of individual atoms in cryoEM maps, the map Q-score. Q-scores can be calculated for atoms in proteins, nucleic acids, water, ligands, and other solvent atoms, using models fitted to or derived from cryoEM maps. Q-scores can also be averaged to represent larger features such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
263
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(293 citation statements)
references
References 34 publications
4
263
0
Order By: Relevance
“…The quality of these models was validated by MolProbity (15) (SI Appendix, Table S1). The Q-scores (16) developed for evaluating the density resolvability were used to assess the quality of these cryo-EM structures (SI Appendix, Figs. S5 and S6).…”
Section: Resultsmentioning
confidence: 99%
“…The quality of these models was validated by MolProbity (15) (SI Appendix, Table S1). The Q-scores (16) developed for evaluating the density resolvability were used to assess the quality of these cryo-EM structures (SI Appendix, Figs. S5 and S6).…”
Section: Resultsmentioning
confidence: 99%
“…Overfitting is one of the main challenges during model refinement and new metrics to detect it are needed (Lawson et al, 2020). The Q-score has been indicated by the authors (Pintilie et al, 2020) that is particularly sensitive to overfitting. Furthermore, we have shown that our method has less dependence on sharpening than the map Q-score and that they complement each other to better estimate the resolvability of atoms.…”
Section: -Discussionmentioning
confidence: 99%
“…The Q-score method measures the correlation between the map values at points around the atom and a reference Gaussian-like function (Pintilie et al, 2020). In this way, the Q-score estimates the resolvability of each atom with respect to the map from which the model has been refined.…”
Section: Fsc-q As a Complement To Q-scorementioning
confidence: 99%
See 1 more Smart Citation
“…We used high-resolution (1.8 Å, EMD-20026) and low-resolution (3.1 Å, EMD-20028) maps of human apoferritin available from the EMDB (Lawson et al, 2011, Pintilie et al, 2020. The crystal structure of human apoferritin (Masuda et al, 2010) was docked into and refined against the 1.8 Å cryo-EM map with the Phenix tools dock_in_map (Liebschner et al, 2019) and real_space_refine .…”
Section: Apoferritin Maps and Modelmentioning
confidence: 99%